Phenomenology of education. In search of the essence of education - Janusz Tomiło (Studia z Teorii Wychowania)
A question about the being of the upbringing is a point of departure for dissertations passed in the article. Appealing to different positions an attempt to portray the phenomenon of the upbringing and ways of understanding him was made. Based on literature studies in the outline an evolution of views on the upbringing, ways of defining the notion and a criticism of the upbringing which happened were portrayed with summons to another above it of thought. He is a purpose of the article - by portraying the dispute about the upbringing - joining in the discourse making aware of both the complexity of the problem and the impossibility of achieving understanding joint and satisfying everyone this phenomenon.